CO2 adsorption on hydroxylated In2O3(110). Issue 39 (9th September 2019) - Posada-Borbón, Alvaro; Grönbeck, Henrik
Abstract : Co-adsorption of H2 modifies CO2 activation on In2 O3 (110). Abstract : Catalytic synthesis of methanol from CO2 is one route to produce added-value chemicals from a greenhouse gas. Here, density functional theory calculations and ab initio thermodynamics are used to study CO2 adsorption on In2 O3 (110) in the presence of H2 and H2 O. We find that the surface is heavily hydroxylated by either H2 or H2 O and that hydroxylation promotes H2 -induced vacancy formation. Moreover, CO2 adsorbs rather in a CO2 − configuration on hydroxylated In2 O3 (110) than on oxygen vacancy sites. The results suggest that hydroxylation-induced oxidation-state changes of In-ions play a significant role in CO2 adsorption and activation during methanol synthesis.